QoS-Aware Virtual Machine Migration in Cloud Environment- A Review - Bhadouria, Vijay; Sandeep Kumar Jain; Avneesh Vashishtha (International Journal of Engineering and Management Research, 2023)
Cloud computing is an evolving field of information technology that allows for online access to computational resources that are maintained in huge data centers. These data centers have physical machine or servers but to fulfill the user request efficiently one physical machine may have several virtual machines. Virtualization technique with the help of hypervisor software serves this purpose. The paper investigates the role of virtualization in providing resources effectively and various parameters involved in live VM allocation. We have also discussed available methods and techniques of virtual machine allocation. Our aim for this review is to boost the chances of delivering unbiased research that accurately reflects the current viewpoint for allocating virtual machines in cloud data centers.